The Effectiveness of the Inquiry-Based Learning Approach in Islamic Education Learning the Material When Life Has Stopped at SD Negeri 106457 Sei Kering - Siregar, Tanti Widyaningsih; Awwaliyah, Wannasiah (Journal of Indonesian Primary School, 2024)
This study aims to test the effectiveness of the inquiry-based learning approach in Islamic religious education learning using student worksheets. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the inquiry-based learning approach is effective in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.71%, the first cycle 66.39% and in the second cycle it increased to 89.66%. Thus, the use of the inquiry-based learning approach can be used as an alternative to improve student learning outcomes in Islamic religious education learning.